Elevated plasma miR-133b and miR-221-3p as biomarkers for early Parkinson’s disease - Qihua Chen (Nature Portfolio, 2021)
Abstract Blood circulating microRNAs (miRNAs) are proposed to be promising biomarkers for many neurodegenerative disorders, including Parkinson’s disease (PD). However, there is a lack of identified differentially expressed miRNAs in PD from different studies. The aim of this study was to evaluate miRNAs expression in PD. We measured plasma circulating miRNA expression in three independent sets with a total of 151 PD patients, 21 multiple system atrophy (MSA) patients and 138 healthy controls using high-throughput RT-PCR. We identified that elevated miR-133b and miR-221-3p discriminated early-stage PD from controls with 94.4% sensitivity and 91.1% specificity. Elevated miR-133b and miR-221-3p distinguished PD from controls with 84.8% sensitivity and 88.9% specificity. In addition, miR-4454 distinguished PD from MSA with 57.1% sensitivity and 82.6% specificity. Hence, elevated miR-133b and miR-221-3p potentially represent good biomarkers for early PD, and a combination of miR-133b, miR-221-3p and miR-4454 has the potential to serve as a non-invasive biomarker for PD diagnosis.